2002
DOI: 10.1038/sj.bjc.6600632
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle behaviours of young adult survivors of childhood cancer

Abstract: This cross-sectional study collected baseline data on the health behaviours of a large population of survivors of childhood cancer in the UK, aged 18 -30 years, compared with those of sex-and age-matched controls. Data from 178 young adult survivors of childhood cancer, diagnosed and treated at Bristol Children's Hospital, 184 peers from the survivors' GP practices and 67 siblings were collected by postal questionnaire. Conditional logistic regression analysis showed that, for matched sets of survivors and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 25 publications
7
86
1
3
Order By: Relevance
“…Findings in the literature are mixed as to whether AYA survivors' engagement in health behaviors is worse or better than that of their healthy peers. 37,38 However, for AYA survivors with suboptimal adherence to recommended health behaviors, supportive care services could be tailored to their needs and address their unique challenges and barriers to accessing such services (e.g., time limitations due to raising young children, financial challenges after cancer treatment, and starting one's career). [39][40][41][42] The current study of AYA cancer survivors and their supporters identified a number of barriers to and facilitators of healthy lifestyle behaviors that could be useful when designing AYA-specific health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the literature are mixed as to whether AYA survivors' engagement in health behaviors is worse or better than that of their healthy peers. 37,38 However, for AYA survivors with suboptimal adherence to recommended health behaviors, supportive care services could be tailored to their needs and address their unique challenges and barriers to accessing such services (e.g., time limitations due to raising young children, financial challenges after cancer treatment, and starting one's career). [39][40][41][42] The current study of AYA cancer survivors and their supporters identified a number of barriers to and facilitators of healthy lifestyle behaviors that could be useful when designing AYA-specific health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Having received highly toxic cardiopulmonary therapy does not appear to modify smoking prevalence. 13 Alcohol use was higher than tobacco use in both groups. No significant differences were found in alcohol or tobacco use by group or age; however, differences were significant by age.…”
Section: Discussionmentioning
confidence: 86%
“…In spite of being a vulnerable population, these survivors display risky behaviors similar to the general population. Although tobacco and alcohol use is generally lower than in the general population, [12][13][14][15]21 there are subsets who frequently abuse alcohol. 14,[22][23][24] Pediatricians are in an exceptional position to promote healthy habits and perform periodic check-ups for an early screening of cardiometabolic complications among ASCC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pese al mayor riesgo de eventos tardíos cardíacos y metabólicos, los sobrevivientes de cáncer son, en su mayoría, sedentarios, consumen frecuentemente tabaco y alcohol, [12][13][14] incluso desde la adolescencia, 15 y no realizan controles médicos regulares. 16 En Argentina, la tasa de incidencia a n u a l d e c á n c e r i n f a n t i l e s d e 124/1 000 000 en menores de 15 años, con un promedio de supervivencia del 65%.…”
Section: Introductionunclassified